(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2020)
The paper aims to examine the dominatus of the Fogliano family, one of the most important lordships in the countryside of Reggio emilia. Articulated around the many fortresses and castles which characterized the region, the seigniory of the Fogliano family was characterized by a substantial overlap, in relation to the exploitation of land and the control over the homines of the communities, between political and economic spaces. In other words, control over the resources of a given area was activated as a result of the domini political affirmation over it. This does not mean, however, that the lordship was folded back on itself: the case study of the dispute between the Fogliano, the Dallo and the commune of Reggio emilia concerning the right to graze on the pastures of the Cusna mountain shows that the lordship was affected by commercial contacts with regions not necessarily close by. Some remarks on the control that the Fogliano family could exercise over the parish churches, the mountain markets and the roads crossing their lordship further enriches the panorama of the lords’ economic spheres of action.